PENETAPAN CUCU SEBAGAI ANAK ANGKAT DAN IMPLIKASINYA TERHADAP MASALAH WARIS - Hotnidah Nasution (AHKAM : Jurnal Ilmu Syariah, 2014)
Determination of Grandson as Adopted Child and its Implications for Inheritance. An application for adoption by an Indonesian Muslim citizen of a Indonesian Muslim child was submitted to the religious court. In the determination the court found a situation where an adopted child was the biological grandchild of the applicant. The method used in this study was normative legal research. The data was analyzed with qualitative methods and explained descriptively. Research results conclude that the grandchild who was the adopted child became an heir through the washiyyah wâjibah to receive at most one third of the inheritance. If the adopted child (grandchild) serves as a substitute heir, then he is not entitled to the last will and testament unless the other heirs agree.DOI: 10.15408/ajis.v14i1.1244